Caracterização fenotípica e genética de bactérias isoladas de sorgo (Sorghum bicolor L. Moench) - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Sorghum is a cereal of great commercial importance. However, this grass does not adapt well to soils of low fertility making the crop dependent on the use of industrial fertilizers. In the quest to address this problem, the benefits that can be provided for interaction between bacteria associated with plants have been the subject of study of various research papers. However, there are currently few studies on bacteria isolated from sorghum. The objective of this work was to characterize polyphase (morphological, biochemical and genetic) of endophytic bacteria isolated from sorghum roots. A total of 24 isolates were selected using the NFb-lactate, LGI-P and YMA semi-insulin medium. The characterization was based on morphological aspects; biochemicals, directed to enzymatic potential and genetic by PCR of the 16S-23S rRNA intergenic region. All isolates were classified as gram-negative and showed high resistance to antibiotics and wide metabolic flexibility regarding the use of different carbon sources. Most of the isolates (95.8%) showed enzymatic activity for catalase, urease, nitrate reductase and nitrogenase. Among the hydrolytic enzymes, the bacteria isolated from sorghum presented higher potential to produce lipases (70.8%) and cellulases (50%). More than 90% of the isolates solubilize phosphate. The analysis of similarity allowed identify morpho-physiological and genetic diversity between the bacteria isolated from the roots of sorghum. It was also possible to verify isolates with mechanisms related to the promotion of plant growth, which can be considered as promising as inoculants or as new sources of enzymes for biotechnological use.
Keywords: Microrganismos endofíticos; Testes bioquímicos; Solubilização de fosfato; Enzimas; PCR 16S-23S; Endophytic microorganisms; Biochemical tests; Phosphate solubilization; Enzymes; PCR 16S-23S; CIENCIAS BIOLOGICAS; BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS